Copyright beyond law : regulating creativity in the graffiti subculture - Iljadica, Marta (Hart, 2019)
The form of graffiti writing on trains and walls is not accidental. Nor is its absence on cars and houses. Employing a particular style of letters, choosing which walls and trains to write on, copying another writer, altering or destroying another writer’s work: these acts are regulated within the graffiti subculture.